2006
DOI: 10.1051/0004-6361:20064918
|View full text |Cite
|
Sign up to set email alerts
|

On the efficiency and reliability of cluster mass estimates based on member galaxies

Abstract: Aims. We study the efficiency and reliability of cluster mass estimators that are based on the projected phase-space distribution of galaxies in a cluster region. Methods. We analyse a data-set of 62 clusters extracted from a concordance ΛCDM cosmological hydrodynamical simulation. We consider both dark matter (DM) particles and simulated galaxies as tracers of the clusters gravitational potential. Two cluster mass estimators are considered: the virial mass estimator, corrected for the surface-pressure term, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
355
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 232 publications
(387 citation statements)
references
References 105 publications
28
355
4
Order By: Relevance
“…In the cluster outskirts, where the virial equilibrium assumption does not hold, the caustic method has yielded promising results for the total cluster masses (e.g., Rines et al 2003;Diaferio et al 2005;Rines et al 2013). The accuracy of dynamical methods was studied in detail by Biviano et al (2006), who found that the virial estimator can recover the virial mass for a galaxy cluster within 10% for samples of at least 60 cluster members. In this sense, the dynamical approach is expensive in terms of telescope time.…”
Section: Optical Scaling Relationsmentioning
confidence: 99%
“…In the cluster outskirts, where the virial equilibrium assumption does not hold, the caustic method has yielded promising results for the total cluster masses (e.g., Rines et al 2003;Diaferio et al 2005;Rines et al 2013). The accuracy of dynamical methods was studied in detail by Biviano et al (2006), who found that the virial estimator can recover the virial mass for a galaxy cluster within 10% for samples of at least 60 cluster members. In this sense, the dynamical approach is expensive in terms of telescope time.…”
Section: Optical Scaling Relationsmentioning
confidence: 99%
“…While at local redshifts dynamical mass estimators can provide robust measurements for relaxed clusters even for rather small spectroscopic samples (e.g. Biviano et al 2006), high redshift systems are particularly prone to be affected by potentially significant biases. In the case of XMMU J1230.3+1339 the fairly low velocity dispersion estimate compared to similarly rich and massive local clusters becomes plausible in the light of the large-scale structure and component analysis in Sect.…”
Section: Velocity Dispersionmentioning
confidence: 99%
“…Though these techniques generate an impression of which galaxies are associated with a cluster, deducing which galaxies are true members of the cluster is often problematic due to interloping galaxies. These interlopers are close to but not gravitationally bound to the cluster and their inclusion can lead to strong bias in velocity dispersion based mass estimates (e.g., Lucey 1983;Borgani et al 1997;Cen 1997; Biviano et al 2006;Wojtak et al 2007; Mamon et al 2010). …”
Section: Introductionmentioning
confidence: 99%